Assessing dystrophies and other muscle diseases at the nanometer scale by atomic force microscopy. (March 2014) - van Zwieten, Ruthger W; Puttini, Stefania; Lekka, Małgorzata; Witz, Guillaume; Gicquel-Zouida, Evelyne; Richard, Isabelle; Lobrinus, Johannes A; Chevalley, François; Brune, Harald; Dietler, Giovanni; Kulik, Andrzej; Kuntzer, Thierry; et al.
Aim: Atomic force microscopy nanoindentation of myofibers was used to assess and quantitatively diagnose muscular dystrophies from human patients.Materials & methods: Myofibers were probed from fresh or frozen muscle biopsies from human dystrophic patients and healthy volunteers, as well as mice models, and Young's modulus stiffness values were determined.Results: Fibers displaying abnormally low mechanical stability were detected in biopsies from patients affected by 11 distinct muscle diseases, and Young's modulus values were commensurate to the severity of the disease. Abnormal myofiber resistance was also observed from consulting patients whose muscle condition could not be detected or unambiguously diagnosed otherwise.Discussion & conclusion: This study provides a proof-of-concept that atomic force microscopy yields a quantitative read-out of human muscle function from clinical biopsies, and that it may thereby complement current muscular dystrophy diagnosis.